Redefinisi Perancah : Potensi Arsitektur Temporer pada Keberlanjutan: Redefining Scaffolding: The Potential of Temporary Architecture in Sustainability - Redyantanu, Bramasta Putra (Universitas Ciputra Surabaya, 2025)
This study explores the potential of scaffolding-based temporary architectural design within the framework of sustainable architecture. Traditionally utilized as a temporary structural element to facilitate construction processes, scaffolding has increasingly evolved into a central component in spatial formation across diverse design contexts. Employing a qualitative case study methodology with research about design approach, this research examines architectural typologies in Indonesia that utilize scaffolding as a fundamental element. The selected case studies span various project scales, encompassing both private and public functions and ranging from small to medium-sized developments. The primary aim of this study is to demonstrate how temporary structural elements can be reimagined as core components in spatial formation, presenting possibilities across various architectural applications. The reflections derived from this investigation are articulated as concepts and ideas that showcase how the temporality of architecture and structural elements can enhance sustainability in design. This study underscores the attributes of flexibility, adaptability, efficiency, and temporality in spaces and buildings formed through scaffolding-based designs. The findings reveal that innovative and creative applications of temporary structural elements as spatial formers hold considerable potential to advance sustainability in architectural discourse. The multifunctionality of such elements paves the way for more exploratory and unconventional design approaches. Additionally, this research highlights that scaffolding, when applied as a primary architectural element, can align with sustainability principles by enabling the creation of efficient, temporary spaces that are both adaptable and flexible. As a result, this study provides valuable insights for practitioners and academics seeking to develop innovative and sustainable approaches in architectural design